The therapeutic effect and safety of the drugs for COVID-19: A systematic review and meta-analysis. Issue 16 (23rd April 2021) - Qiu, Rong; Li, Jingwei; Xiao, Yuxuan; Gao, Ziyi; Weng, Yihang; Zhang, Qiran; Wang, Chengdi; Gong, Hanlin; Li, Weimin
Abstract: Background: Coronavirus disease 2019 (COVID-19) has spread almost all regions of the world and caused great loss to the whole body of mankind. Thus, numerous clinical trials were conducted to find specific medicine for COVID-19 recently. However, it remains unanswered whether they are beneficial. Objective: This study aimed to evaluate the efficiency and safety of the COVID-19 medicine. Methods: Studies were determined through searching PubMed, Embase, Cochrane Library, and Medline. The studies of COVID-19 medicine were involved with eligible end points containing mortality, discharge rate, rate of clinical improvement, and rate of serious adverse events. Results: A total of 33 studies involving 37, 879 patients were included in our study, whose intervening measures contained three major types of COVID-19 medicine, ACEI/ARB, antiviral medicine, and chloroquine/hydroxychloroquine. Compared to control group, COVID-19 drugs have no distinct effect on mortality (RR, 0.93; 95% CI, 0.79–1.11, P  = .43) and discharge rate (RR, 1.06; 95% CI, 0.98–1.14, P  = .13). However, antiviral medicine presents the obvious advantage in clinical improvement (RR, 1.11; 95% CI, 1.01–1.23, P  < .05). In addition, the serious adverse events rate (RR, 0.75; 95% CI, 0.63–0.88, P  < .05) of COVID-19 medicine is lower than control group. Conclusion: The results indicated antiviral medicine was potential specific medicine for COVID-19 treatment by improving clinical symptoms, but it failed to increase the discharge rate and reduce mortality. Chloroquine/hydroxychloroquine and ACEI/ARB had no significant effect on treatment of COVID-19, thus they were not recommended for routine medication. Moreover, more trials are needed to find effective drugs to lower the mortality of COVID-19 patients. Abstract : Supplemental Digital Content is available in the text